LEGAL PROTECTION OF E-CONSUMERS IN MALAYSIA - Amirah Khadijah Roslan; Nik Syairah Amalin Mohd Fakrudin; Nur Amalina Abdul Ghani; Hasbollah Mat Saad; Suhaili Ishak, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
E-commerce has experienced tremendous growth in recent years. The popularity of online shopping continues to grow. Many e-commerce applications are being launched rapidly in Malaysia, posing a legal protection issue for e-customers. This study aims to analyze the law in Malaysia protecting e-consumers, determine whether they are adequate, and investigate whether they are aware of their legal rights. A large number of online retailers have transformed the way we do business. Among the subjects of the study were the laws available to protect consumers, the effectiveness of those laws, as well as the awareness of e-consumers of their rights. These data were collected using quantitative sampling techniques, data collection processes, and data analysis techniques. Survey data was collected by posting a 100-sample Google form survey across various platforms to reach the target groups. Initially, the results of the survey suggested that Malaysian laws do not adequately protect e-consumers. The lack of robust and adequate laws to protect consumers online is apparent in Malaysia. It is recommended that Malaysia enact the Malaysian E-Consumer Law to protect e-consumers in Malaysia.